Intellectual functioning and executive functions in children and adolescents with attention deficit hyperactivity disorder (ADHD) and specific learning disorder (SLD). Issue 5 (26th June 2019) - Faedda, Noemi; Romani, Maria; Rossetti, Serena; Vigliante, Miriam; Pezzuti, Lina; Cardona, Francesco; Guidetti, Vincenzo
Abstract : Several studies have shown neuropsychological deficits across multiple domains in attention deficit hyperactivity disorder (ADHD) and specific learning disorder (SLD), but differences and similarities between these disorders have been little considered. We were interested in analyzing the intellectual and executive profiles in a sample of children and adolescents, divided according to the diagnosis into the ADHD group and the SLD group, and in identifying the differences and similarities between these disorders. The sample included two clinical groups: the first included 36 children and adolescents with a diagnosis of ADHD (5–15 years; mean = 9.42; SD = 2.22) while the second included 36 children and adolescents with a diagnosis of SLD (7–15 years; mean = 9.43; SD = 2.25). The WISC‐IV was used to measure intellectual ability and the NEPSY‐II was employed to measure executive functions. The results showed that the SLD group had significantly higher scores than the ADHD group on the NEPSY‐II in the inhibition, cognitive flexibility, short‐term verbal memory and verbal working memory domains. The ANCOVA showed differences regarding the FSIQ of WISC‐IV, in that the SLD group obtaining higher scores than ADHD group. Findings showed that ADHD children are more impaired than SLD children, in particular in cognitive inhibition, cognitive flexibility, verbal memory, working memory and intellectual functioning. The recognition of the strengths and weaknesses of children and adolescents with ADHD and SLD allows to outline an educational and clinical intervention focused on their specific executive and intellectual functioning.